Parents' reaction toward public elementary instruction in Tuguegarao - Gonzaga, Thelma (Reyes) 1931- ([Quezon City s.n.], 1970)
The purpose of the study is to determine the reactions of selected parents toward public elementary instruction in Tuguegarao, with emphasis on the personal and professional qualities of teachers, teacher's work, curricular and co-curricular offerings of the public elementary schools and the Parent-Teacher Association. Results of the study may provide policy-makers with bases to consider in promulgating educational policies.
Thesis (M.Ed.)--University of the Philippines
Keywords: Home and school